2012
DOI: 10.1186/1297-9686-44-2
|View full text |Cite
|
Sign up to set email alerts
|

The genetic parameters of feed efficiency and its component traits in the turkey (Meleagris gallopavo)

Abstract: Residual feed intake (RFI) and feed conversion ratio (FCR) can be incorporated into a breeding program as traits to select for feed efficiency. Alternatively, the direct measures used to calculate RFI and FCR can be analyzed to determine the underlying variation in the traits that impact overall efficiency. These constituent traits can then be appropriately weighted in an index to achieve genetic gain. To investigate feed efficiency in the turkey, feed intake and weight gain were measured on male primary breed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
40
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 13 publications
7
40
6
Order By: Relevance
“…They were within the limits of published data in beef cattle, pigs and turkeys [5,6,8,21,22]; selection for low RFI will improve feed efficiency with an expected correlated response in FI. Based on the genetic correlation between RFI and metabolic body weight as obtained, it could be mentioned that this would favor obtaining a lower maintenance energy requirement in ducks.…”
Section: Discussionsupporting
confidence: 77%
“…They were within the limits of published data in beef cattle, pigs and turkeys [5,6,8,21,22]; selection for low RFI will improve feed efficiency with an expected correlated response in FI. Based on the genetic correlation between RFI and metabolic body weight as obtained, it could be mentioned that this would favor obtaining a lower maintenance energy requirement in ducks.…”
Section: Discussionsupporting
confidence: 77%
“…For example, Nestor et al (1967) summarised heritability estimates of BW as ranging from 0.36 to 0.42 in the different age groups from 0 to 24 weeks of age. Case et al (2010) reported values of 0.35 6 0.02 for the heritability of BW at 15 weeks with the bivariate method. Chapuis et al (1996) reported heritability estimates of 0.77 for female BW and 0.68 for male BW at 16 weeks of age.…”
Section: Heritabilitymentioning
confidence: 99%
“…milk and egg production or in this case body weight gain) and body weight maintenance [6]. Some of the cited advantages of RFI are that it is heritable, moderately correlated with FCR and feed intake, and ideally, independent of production traits [6,7]. Although RFI may be seen as a good indicator of feed efficiency, it does have its drawbacks, namely, slow growing animals eating a relatively small amount of feed may have a more favorable RFI value [8].…”
Section: Introductionmentioning
confidence: 99%
“…Although RFI may be seen as a good indicator of feed efficiency, it does have its drawbacks, namely, slow growing animals eating a relatively small amount of feed may have a more favorable RFI value [8]. Previously reported heritability estimates for FCR and RFI in the turkey were 0.22 and 0.24, respectively, with a genetic correlation of 0.80 [7]. …”
Section: Introductionmentioning
confidence: 99%